Strategic Alliances and Marketing Orientation: to Improve SME’s Performance - Kesi Widjajanti; Phimlikid Kaewhanam; Vini Wiratno Putri (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2023)
The objectives of this study is to develop a basic conceptual model for predicting the best relationship between management resources, management process, strategic alliance, market orientation, and performance. This study would like to outline the strategy for enhancing performance of SMEs through alliances. The study of strategic alliances is a business strategy that has been adopted by various large organizations for improving the company performance. However, the application of strategic alliances in small and medium enterprises (SMEs) has not been examined comprehensively. Primary data were collected from 105 SME managers in Jepara, Central Java, Indonesia. The study employed structural equation model (SEM) to set up the relationship among variable. The results indicated that strategic alliance did not influence directly to the company’s performance. In addition, indirect effect of market orientation as a mediating variable might increase the company performance as compared to the direct effect of strategic alliance. The contributions of the theory support the strengthening of Resource Based View that proved the influences of an exchange of management resources as a perspective of strategic alliance to motivate the company for impoving its performance. This research provides managerial implications to improve performance of SMEs, whereby company must not only simply form strategic alliance, but also must also have access vital resources so that market orientations can be strengthened.